Overview on synthesis of magnetic bio char from discarded agricultural biomass - Tripathi, M.; Mujawar, Mubarak; Sahu, J.; Ganesan, P. (Scrivener Publishing LLC, 2017)
© 2017 Scrivener Publishing LLC. Agricultural waste biomass is present in a large quantity in most of the countries have considered to be a suitable material for many applications because of their abundance, degradability and low cost. Agricultural wastes have been successfully converted into bio char by means of pyrolysis or other thermochemical conversion techniques. The bio char obtained from agricultural wastes are highly porous and thus are very useful in the adsorption applications. Moving one step ahead these bio char materials have been doped with magnetic medium to convert them in magnetic bio char as mmagnetic separation technology is an efficient technology for the separation of magnetic materials which is used for many applications in environmental technology, analytical chemistry and mining, medicine, diagnostics and cell biology. These magnetic bio char materials, with the combination of high porosity along with optimized magnetic properties have been successfully utilized in the adsorption of heavy metals, various organic and inorganic chemicals including phenol, tetracycline etc. The major advantage of magnetic bio char is that the magnetic bio char even with low BET surface area and low total pore volume can exhibit high adsorption capacity because more metal ions per unit surface area of magnetic bio char can be adsorbed easily. Moreover, the sorption of magnetic bio char from the aqueous solution is very simple and effective and thus neutralizes the issue of secondary pollution. It can be re-used after the regeneration, thus making the whole adsorption process economically viable and more environment friendly. Bio-polymer based magnetic bio char has tremendous applications in biomechanical engineering and medical science since it can serve the purpose of drug carrier very efficiently in magnetic drug delivery systems which is utilized in the treatment of cancer and other diseases. Magnetic bio char with so many potential applications has been synthesized by a number of researchers using different techniques, and different combination of agricultural waste/activated carbon and chemicals. In this chapter we have discussed the various synthesizing techniques which have been adopted by the researchers to prepare magnetic bio char. The BET surface area and magnetic characteristics along with their potential applications and future scope of the magnetic bio char have also been given a notice in the present chapter.